ESP: THE DEVELOPMENT AND THE CHALLENGES - Umar, Umar -; Basuki, Slamet (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
The term "English for Specific Purposes" (ESP) refers to a method of teaching English that is centered on the learner's objectives and needs. The ESP technique is a well-liked option in the context of learning English in Indonesia, both at higher schools or universities, especially for students outside of the English major. This method is also consistent with government policies in the area of education, which place an emphasis on the goals of learning English, namely to improve students' proficiency in using English, particularly for academic needs and professional careers with an emphasis on reading skills that enable students to understand authentic material topics relevant to their majors and effectively. This study uses library research, which compiles extensive documentation on a single or a number of topics. Both original sources and secondary sources are used in this investigation. This article presents theoretical research on the following development and challenges: The Fundamental Idea Regarding English for Specific Purposes (ESP); The Needs Analysis Function in ESP; ESP as a Method for Teaching Languages; Curriculum for ESP; ESP Curriculum Design and Goals for teaching ESP